Impact of Jurisprudence Adaptability Change on Judging and Activities of Investment under Proxy Product in Islamic Financial Institutions - Alhadiyah, Mohammad Ali (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: The investment agency is considered the most widely implemented financial product in Islamic investment institutions. This research aims to highlight the impact of juristic adaptation in regulating the operations of Islamic institutions and its effect on the investment agency product in Islamic financial institutions. Methods: The study followed a descriptive approach by collecting statements and adaptations from their sources. It also employed a comparative method in presenting juristic issues and an analytical method in discussing opinions and evidence. Results: The study concluded that juristic adaptation of the investment agency contract is determined according to the purpose for which this contract is used. In deposits and savings, the agency is unrestricted to the financial institution. However, when using the agency to deal with other financial institutions or to provide liquidity, the agency is restricted and may be combined with contracting for oneself. The study also found that the reason for changing from unrestricted agency to restricted agency is the change in the method of using this investment product to meet financing needs. Conclusions: The study emphasizes the importance of studying the juristic adaptation of the agency contract product and that the juristic rulings for the investment agency product vary based on the juristic adaptation of the contract. The study recommends researchers to study the impact of juristic adaptations on juristic rulings in various Islamic finance products.